1999
DOI: 10.4049/jimmunol.163.2.963
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide Modulates Cyclooxygenase-2 Transcriptionally and Posttranscriptionally in Human Macrophages Independently from Endogenous IL-1β and TNF-α

Abstract: The pathogenesis of septicemia can be triggered by LPS, a potent stimulus for PG synthesis. The enzyme cyclooxygenase (COX) is a rate-limiting step in PG production. COX exists as two isoforms: COX-1, which is constitutively expressed in most cell types, and COX-2, which is inducible by LPS and cytokines in a variety of cells. In this study we determined the role of the proinflammatory cytokines IL-1β and TNF-α released by LPS-stimulated U937 human macrophages in the regulation of COX-2. Macrophages exposed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…After application of IPA to the significant genes in humans we identified a top network, LPS, which included PTGS2 , as LPS is a known COX2 activator. 23 Third, using the genes identified in the mouse sc-58125 network, we tested for enrichment in the human data and found the network genes to be highly significantly enriched in humans (empirical P =0.00008). We believe the 3 different validation methods establish in humans the importance of this COX2 network identified in the high-dimensional mouse data set.…”
Section: Discussionmentioning
confidence: 99%
“…After application of IPA to the significant genes in humans we identified a top network, LPS, which included PTGS2 , as LPS is a known COX2 activator. 23 Third, using the genes identified in the mouse sc-58125 network, we tested for enrichment in the human data and found the network genes to be highly significantly enriched in humans (empirical P =0.00008). We believe the 3 different validation methods establish in humans the importance of this COX2 network identified in the high-dimensional mouse data set.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the co-treatment with LPS and indomethacin, AgL3OAc, or AuL3 (Figure 6a, panels 3, 4, and 6B, respectively) produced no difference Together with iNOS, COX-1 and COX-2 are important pro-inflammatory proteins involved in the synthesis of prostaglandins (PGs) from arachidonic acid and are inhibited by nonsteroidal anti-inflammatory drugs (NSAIDs) [63]. It is well known that COX-1 is constitutively expressed in most human tissues, while COX-2 expression is induced by inflammatory stimuli, including LPS and cytokines, in macrophages [64,65].…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%
“…18 In contrast, COX-2 is less widely expressed, but its expression is induced upon activation by proinflammatory mediators, like interleukin 1, tumor necrosis factor α, lipopolysaccharides, and tumor promotors. 19 Although it is generally stated that COX-1 is not involved upon immune activation, its role in inflammation should not be underestimated. Studies in animal models have shown that COX-1 serves an important role in the development of inflammatory sequelae like edema.…”
mentioning
confidence: 99%